MEMAHAMI DAN MEMAKNAI BERBAGAI PERATURAN, KETETAPAN, DAN HUKUM DALAM TAURAT - Raikhapoor Raikhapoor (Jurnal Christian Humaniora, 2020)
This paper discusses various kinds of provisions, regulations and laws in the Torah. Generally, the perspective about the Torah is often too narrow and simple, even though the understanding of the Torah is actually broad. Our view of the Torah often refers only to the laws, rules and regulations of the Old Testament. This view is produced by understanding the New Testament which results in the Torah being seen as a part that produces rigid laws that often have negative tendencies. To overcome this problem, I want to give a more comprehensive explanation about the various rules and regulations in the Torah.BAHASA INDONESIA ABSTRACT: Artikel ini membahas berbagai macam ketetapan, peraturan dan hukum dalam Taurat. Secara umum, pandangan tentang Taurat seringkali terlalu sempit dan sederhana, seringkali hanya merujuk pada hal-hal yang berkaitan dengan hukum-hukum, peraturan-peraturan atau regulasi-regulasi. Pandangan yang demikian menghasilkan pandangan yang bertendensi negatif dan keliru akan Taurat. Taurat dipahami sebagai suatu kitab yang dipenuhi kekakuan, padahal mestinya tidak demikian. Untuk mengatasi masalah ini, penulis ingin memberikan penjelasan yang lebih komprehensif tentang berbagai peraturan dan ketetapan dalam Taurat.Keywords: Torah, instruction, teaching, law